2023
DOI: 10.1200/po.22.00447
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a Cross-Ancestry Polygenic Model With Clinical Risk Factors Improves Breast Cancer Risk Stratification

Abstract: PURPOSE To develop and validate a cross-ancestry integrated risk score (caIRS) that combines a cross-ancestry polygenic risk score (caPRS) with a clinical estimator for breast cancer (BC) risk. We hypothesized that the caIRS is a better predictor of BC risk than clinical risk factors across diverse ancestry groups. METHODS We used diverse retrospective cohort data with longitudinal follow-up to develop a caPRS and integrate it with the Tyrer-Cuzick (T-C) clinical model. We tested the association between the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The addition of the PRS increased the AUC in both models, from 0.56 to 0.59 in the BCRAT and from 0.51 to 0.55 in the IBIS model. Most recently, Tshiaba et al have evaluated the addition of a cross-ancestry PRS [ 40 ] to the IBIS model in data from the Women’s Health Initiative and the UK Biobank [ 41 ]. Across all ancestry groups, the addition of the PRS to the IBIS model increased the AUC for prediction of risk in the next five years from 0.56 to 0.65 in the WHI and from 0.57 to 0.63 in the UK Biobank.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of the PRS increased the AUC in both models, from 0.56 to 0.59 in the BCRAT and from 0.51 to 0.55 in the IBIS model. Most recently, Tshiaba et al have evaluated the addition of a cross-ancestry PRS [ 40 ] to the IBIS model in data from the Women’s Health Initiative and the UK Biobank [ 41 ]. Across all ancestry groups, the addition of the PRS to the IBIS model increased the AUC for prediction of risk in the next five years from 0.56 to 0.65 in the WHI and from 0.57 to 0.63 in the UK Biobank.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, by combining estimates from the previously validated BWHS breast cancer risk prediction model with the newly validated AA-PRS, we now have a combined model that provides discriminatory accuracy higher than the BWHS model alone and similar in magnitude to combined models in women of European ancestry. Cross-ancestry models are being put forth as valuable for multiple ancestral populations, but, to date, show relatively poor performance in African ancestry populations [ 41 ]. To develop a cross-ancestry PRS that works well for all major population groups, it will be necessary to have larger numbers of cases and controls from African ancestry populations and from other populations currently underrepresented in genetics research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study of blood lipid levels showed that PGS constructed using multi-ancestry GWAS outperforms those constructed using single-ancestry matched data [ 118 ]. A larger analysis of 14 disease endpoints results from the Global Biobank Meta-analysis Initiative (GBMI) also concluded that using multi-ancestry GWAS improved the accuracy of PGS for all ancestries, although a significant amount of heterogeneity in accuracy exists across ancestries [ 119 ], and many other PGS based on multi-ancestry GWAS can be validated in diverse populations [ 46 , 120 , 121 ]. However, multiple studies constructing and evaluating PGS in African populations have come to the opposite conclusion that ancestry-matched PGS is most optimal for the prediction [ 25 , 115 , 122 , 123 ].…”
Section: Analytic Challenges For Translation Of Polygenic Scoresmentioning
confidence: 99%